'#YouCanTalk': A multimodal discourse analysis of suicide prevention and peer support in the Australian BeyondBlue platform. Issue 2 (April 2020) - Sindoni, Maria Grazia
Research has shown that suicide rate in Australia is on the rise and that most people who die by suicide are not in contact with mental health services. They most likely communicate their suicidal thoughts to family members or close friends, whose responses may sound unhelpful and/or dismissive, thus reinforcing suicidal ideation. This national emergency has been tackled via a social media campaign, #YouCan Talk, launched by a government-supported digital platform, BeyondBlue. This article adopts a multimodal discourse analysis approach to investigate how peer support is encouraged and articulated in the context of mental health discourse for suicide prevention. The two case studies selected for analysis from the BeyondBlue platform are (1) the #YouCanTalk social media campaign, designed to teach carers to identify severe depression and effectively respond to suicide warning signs and (2) a sample of posts from a thread for peer support in a monitored online forum devoted to help carers who seek peer advice. Unlike previous research, the article focuses on how pronouns and verbs index interpersonal relations in a systemic-functional perspective as well as other multimodal resources, such as visuals, layout and hyperlinking, to understand how identities are entextualised by both professional health providers and peer carers in digital platforms that address mental health issues.